2019
DOI: 10.3390/jcm8091285
|View full text |Cite
|
Sign up to set email alerts
|

Right Heart Remodeling in Patients with End-Stage Alcoholic Liver Cirrhosis: Speckle Tracking Point of View

Abstract: Background: Data regarding cardiac remodeling in patients with alcoholic liver cirrhosis are scarce. We sought to investigate right atrial (RA) and right ventricular (RV) structure, function, and mechanics in patients with alcoholic liver cirrhosis. Methods: This retrospective cross-sectional investigation included 67 end-stage cirrhotic patients, who were referred for evaluation for liver transplantation and 36 healthy controls. All participants underwent echocardiographic examination including strain analysi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…In our study, using speckle-tracking strain analysis, we showed that RV-GLS measurements were significantly lower in patients with cirrhosis than in controls. Our results are similar to those of other studies that found reduced RV strain in patients with cirrhosis [19,21]. In addition, in our study, RV-GLS measurements were lower in patients with ascites than in patients without.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In our study, using speckle-tracking strain analysis, we showed that RV-GLS measurements were significantly lower in patients with cirrhosis than in controls. Our results are similar to those of other studies that found reduced RV strain in patients with cirrhosis [19,21]. In addition, in our study, RV-GLS measurements were lower in patients with ascites than in patients without.…”
Section: Discussionsupporting
confidence: 93%
“…RV function is more difficult to evaluate than LV function. The fine changes in the systolic and the diastolic functions of the heart, which can be seen in cirrhotic patients, may not be detected with the conventional transthoracic echocardiography [19]. Novel echocardiographic techniques can improve the quantitative assessment of RV function.…”
Section: Discussionmentioning
confidence: 99%
“…There were four cross-sectional [ 11 , 45 , 46 , 48 ], five case-control [ 10 , 49 52 ], five prospective cohort studies [ 36 , 54 , 56 58 ] providing results only for the left ventricle. Meanwhile, one cross-sectional study [ 47 ] providing result only for the right ventricle. There were two case-control studies [ 10 , 52 ] in which evaluations were performed using CMR and others using 2D-STE.…”
Section: Resultsmentioning
confidence: 99%
“…There were two case-control studies [ 10 , 52 ] in which evaluations were performed using CMR and others using 2D-STE. Five cross-sectional [ 11 , 15 , 45 , 47 , 48 ], three case-control [ 50 , 51 , 53 ], and five prospective cohort studies [ 14 , 36 , 54 , 57 59 ] used the EchoPAC system; one cross-sectional [ 46 ], one case-control [ 49 ], and one prospective cohort study [ 55 ] used Velocity Vector Imaging and one prospective cohort study [ 56 ] used the QLAB system for 2D-STE evaluation. The etiology of cirrhosis varied; the most common etiologies were hepatitis B and C viruses [ 10 , 14 , 15 , 36 , 45 , 46 , 48 , 49 , 52 – 54 , 56 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al, found that in alcoholic cirrhotic patients RA maximal area and RA volume index were higher and both RA and RV functions deteriorated. Unfortunately, in that study the influence of alcohol on right heart functions could not be excluded [32]. Patients with increased RA pressure before and after transjugular intrahepatic portosystemic shunt (TIPS) had approximately twice the mortality of those with normal RA pressure [33].…”
Section: Original Articlementioning
confidence: 96%